Akad-Akad Transaksi Perbankan Syariah Dalam Tinjauan Studi Hadits - Sahudi, Sahudi (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2024)
This study aims to describe and analyze 1) contracts in Islamic banking, 2) hadith about contracts in Islamic banking transactions, 3) implementation of hadith in Islamic Banking transactions. The research method uses the interpretation research method, with a descriptive analysis method. The hadith studies used in this study are in the following arrangement: 1) hadith texts and sanad hadith, 2) translation of hadith, 3) brief biography of sanad / hadith scholar, 4) analysis of hadith, 5) implementation of hadith in Islamic Banking transactions. The results of the study 1) contracts in Islamic Banking transactions consist of a) Mudharabah, b) Musyarakah, c) Murabahah, d) Ijarah, e) Qard al Hasan, f) Wakalah, g) Kafalah; 2) In general, hadith in the context of Islamic banking transactions serves to show the validity of a contract and provide guidance in carrying out these transactions in sharia. The hadith is also evidence of the initial agreement between the parties involved in Islamic banking transactions and serves as a handle in resolving disputes in the event of a dispute between them; 3) In mudharabah and musyarakah agreements, banks and customers share risks and benefits with each other. It aims to encourage partnerships and cooperation in business, as well as minimize the risk of failure. In its application, Islamic banking follows islamic sharia rules and principles, including in determining profits and risks that must be shared fairly between banks and customers.